Обзор документов фонда Таврического и Одесского караимского духовного правления из Государственного архива в АР Крым - Прохоров, Д.А.; Белый, О.Б. (Материалы по археологии, истории и этнографии Таврии, 2008)
Исследования по истории, этнографии и культуре караимов в последние годы приобрели особую актуальность. Связано это, прежде всего, с позитивными тенденциями, набирающими силу в отечественной науке, ее демократизацией и избавлением от целого ряда стереотипов и политической заангажированности. Воссоздание прошлого крымских караимов на сегодняшний день является одной из наиболее актуальных проблем в изучении тюркоязычных народов Крыма. Reconstruction of the past of the Crimean Karaims is one of the most actual problems in studying of Turkish-speaking people of the Crimea. The history of creation and activities of Taurica and Odessa Karaims Clerical Administration (TOKCA) -the central organ of confessional self-government of the Karaims of the mid-19ер - the beginning of the 20th centuries - is one the most insufficiently studied pages of the Karaims’ history. It should be noted that this topic has not been considered in our historiography. As the result of the work with the materials of fund 241 of «Taurica and Odessa Karaims Clerical Administration» of the National Archive in the Autonomous Republic of Crimea some dozens of cases were examined; they contain various information on the activities of organs of confessional self-government of the Karaims of the Russian Empire during almost 80 years.